The Influence of Personnel Competence, Facility Reliability and Speed of Process on Customer Satisfaction through Service Performance at Terminal 3 of Soekarno-Hatta International Airport - Anindita Galuh Wardhani; Juliater Simarmata; Edi Abdurachman (Dinasti Review, 2025)
This study examines the influence of personnel competence, facility reliability, and process speed on service performance and customer satisfaction, as well as examining the mediating role of service performance in the relationship between the independent variables and customer satisfaction at Terminal 3 of Soekarno-Hatta International Airport. A quantitative approach was employed using the SEM-PLS data analysis technique. Data were gathered through a survey involving 410 passengers at Terminal 3 of Soekarno-Hatta International Airport. The results of the study indicate that personnel competence, facility reliability, and process speed have a significant positive impact on both service performance and customer satisfaction. Furthermore, service performance is found to successfully mediate the relationship between the three independent variables and customer satisfaction. Based on these findings, it is recommended that the management of Terminal 3 at Soekarno-Hatta International Airport enhance personnel training, ensure optimal facility maintenance, and implement digitalization and automation technologies to expedite service delivery.